THE INFLUENCE OF FARMERS' BEHAVIOR ON THE USE OF CERTIFIED RICE SEEDS IN UJUNG TANAH VILLAGE, MARE DISTRICT, BONE REGENCY - Sarah, Selvani; Suradi, Adam Rahman; Ramli, Fatmawati (Universitas Veteran Bangun Nusantara, 2025)
The use of certified rice seeds plays an essential role in improving rice productivity and ensuring high quality harvests. However, in practice, many farmers have not utilized certified seeds optimally. Farmers behavior is considered one of the factors influencing decision to use certified seeds. This study aims to analyze the effect of farmers behavior on the use of certified rise seeds in Ujung Tanah Village, Mare District, Bone Regency. This research was conducted from March to April 2025 using a quantitative approach with a survey method. Respondents were determined using a simple random sampling method of 48 farmers. Data were collected using a questionnaire and analyzed using multiple linear regression. The results show that knowledge, attitudes, and skills simultaneously influence the use of certified rice seeds. Partially, knowledge does not have a significant effect, while attitudes and skills significantly effect the use of certified seeds. This indicates that the better the farmers attitudes and skills, the higher farmer tendency to adopt certified rice seeds. Keywords: Certified seed, Farmer behavior, Knowledge, Attitude, Skills